The effects of cultivar mixtures on insect pest and natural enemy abundance, diseases, and yield in tropical soybean cropping system - Sokha Kheam; Diana Rubene; Dimitrije Markovic; Saveng Ith; On Norong Uk; Soth Soung; Velemir Ninkovic (Biological Control, 2024)
Increasing genotypic crop diversity via cultivar mixtures is a promising sustainable approach to control insect pests and diseases, thereby improving yield. The effects of genotypic diversity have not been studied for many crops. We investigated the effects of cultivar mixtures in a tropical soybean (Glycine max L. Merrill) cropping system on i) insect pest abundance, ii) natural enemy abundance, iii) diseases, and iv) yield. In the field trial, three soybean cultivars were used, two commercial and one traditional, with a randomized complete block design. Significant differences among cultivars and some mixtures were found for certain insect pest abundance (whitefly and brown bean bug), but no consistent mixture effects were observed. Significant increases in natural enemies (predatory ant, lady beetle, parasitoid wasp, and dragonfly) were detected in some cultivar mixtures, compared to single cultivars. Higher genetic diversity in cultivar mixtures increased the abundance of certain natural enemies at specific plant stages. The cultivar mixtures did not alter disease symptoms or yield. These results were obtained during a season with very low overall pest pressure, and the effects of cultivar mixtures might be altered at higher pest pressure, which should be further investigated. This study highlights trade-offs in cultivar selection when jointly considering pest and disease abundance and yield, as no single cultivar (or mixture) performed better in all observed aspects. Our study supports the hypothesis that increasing cultivar mixtures can promote the abundance of certain natural enemies, suggesting the potential of cultivar mixture effects for biological control and sustainable agricultural management.